Integrating Halal Awareness and Islamic Economic Values: A Conceptual Framework for Muslim Students' Consumption Behavior - Mayang, Sekar; Putri Puspita Sari, Anugrah Mustika (The Postgraduate of Institut Agama Islam Negeri Metro Lampung, 2025)
Introduction: The growing complexity of halal consumer behavior in contemporary Muslim societies underscores the need for a more integrated theoretical framework that integrates the cognitive, ethical, and behavioral dimensions. Objective: This research aims to conceptualize halal awareness as a multidimensional construct encompassing knowledge and ethical sensitivity. And concern in Muslim consumer behaviour. Method: This study employs a qualitative conceptual research design. The study employs an integrative literature review supported by thematic analysis to synthesize insights from peer-reviewed journals, classical and modern Islamic economics literature, and reports from the halal industry. Result: The findings show that halal awareness is multidimensional, encompassing knowledge, ethical sensitivity, and concern, while Islamic economic values introduce deeper moral principles such as maslahah, ʿadl, halalan tayyiban, iḥtiyāth, and moderation. Implication: This suggests that combining planning, implementation, and evaluation in a foundational framework that can guide future empirical research, inform policy in halal governance, and support the Development of educational and industry strategies that promote ethical, value-based halal consumption.